A retrospective cohort study assessing the incidence of inferior vena cava (IVC) occlusion following prophylactic IVC filter insertion: Is anticoagulation necessary during filter dwell?. Issue 8 (August 2022) - Clements, Warren; Marshall, Elissa; Lukies, Matthew; Joseph, Tim; Tran, Huyen; Ban, Ee Jun; Koukounaras, Jim
Highlights: This study assessed the incidence of IVC thrombosis following prophylactic filter insertion at a tertiary trauma centre. 124 patients were included and were no cases of IVC occlusion in any of the groups. The use of therapeutic anticoagulation during IVC filter dwell should not be dictated by the presence of an IVC filter but rather by the presence of a related thrombosis event. Abstract: Background: Inferior vena cava (IVC) filters play a role in preventing venous thromboembolism after major trauma where deep venous thrombosis (DVT) risk is up to 80%. It has been suggested that IVC filters are thrombogenic and many patients are therefore placed on therapeutic anticoagulation during IVC filter dwell citing concern of in situ IVC thrombosis, even in the absence of existing DVT. Methods: Between 1 June 2018 and 31 December 2021, this retrospective study assessed the incidence of IVC thrombosis following prophylactic IVC filter insertion. Groups were defined according to the presence or absence of therapeutic anticoagulation during filter dwell. The primary outcome was the presence or absence of IVC thrombus at retrieval. Results: A total of 124 patients were included. Anticoagulation was prescribed in 29 and anticoagulation was not prescribed in 63. A further 32 patients developed a new thrombosis episode after the prophylactic IVC filter was placed, and 29 were prescribed anticoagulation part-way during filter dwell as a result of this diagnosis. No cases of IVC occlusion were observed in any patient group. Conclusions: Caval thrombosis was not observed after prophylactic filter placement, with or without the prescription of anticoagulation. While prospective trials are needed to increase the level of evidence, based on these results the use of therapeutic anticoagulation during IVC filter dwell should not be dictated by the presence of an IVC filter alone but rather by the presence of a related thrombosis event.